Pemberdayaan Lahan Kering untuk Pengembangan Agribisnis Berkelanjutan - Bambang Irawan; Tri Pranadji (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2002)
EnglishUtilization of dry land for farming activities in Indonesia is presently less optimal compared with its availability. In order to overcome the